Investment and Financial Constraints in European Agriculture: Evidence from France, Hungary and Slovenia - Imre Fertő; Zoltán Bakucs; Štefan Bojnec; Laure Latruffe (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2012)
The article investigates the investment and financial constraints for French, Hungarian and Slovenian farms using FADN panel data with different econometric estimation approaches. Farm gross investment is positively associated with real sales growth and cash flow implying the absence of soft budget constraint. Gross farm investment is positively associated with investment subsidies. Specific results by country are found depending on farm indebtedness. Investment subsidies can mitigate some capital market imperfections in short-term, while on long-term what is crucial is farm sale ability to successfully compete in the output market gaining sufficient cash flow for farm competitive survival and investment.
Keywords: D81; D92; O12; Q12; C23; 330; farm investment; soft budget constraint; investment subsidy; panel data analysis; Landwirtschaft; Investition; Budgetrestriktion; Investitionspolitik; Panel; Frankreich; Ungarn; Slowenien